Quantum-inspired entanglement between collaborating brains during human memory encoding - Xue Yang; Yi Jiang; Qianxiang Zhou; Kuan Pei; Chunyan Guo; Peng Zhang (Proceedings of the National Academy of Sciences, 2026)
The extent to which two brains align during information processing is thought to be central to collaborative memory encoding; however, the neural mechanisms that support such interpersonal alignment remain elusive. Traditional interbrain synchrony models based on phase-alignment metrics fail to distinguish true interbrain connectivity from spurious synchrony driven by shared stimulus processing. Here, we introduce a quantum-inspired framework to capture the connectivity between two collaborating brains. Using dual-brain Electroencephalogram (EEG) hyperscanning, we quantified interbrain coupling during collaborative (Colla)-memory and independent (Indep)-memory encoding in two experiments, including 70 dyads (N = 140) in Experiment 1 and 41 dyads (N = 82) in Experiment 2, which incorporated an empathy-enhancement training procedure. Treating Indep as a baseline state, we found that Colla without training deviated from this baseline by showing a higher probability of aligned states and a lower probability of misaligned states. Following empathy enhancement, Colla state probabilities returned toward the Indep baseline, accompanied by parallel normalization in memory retrieval performance and a shift in the cortical distribution of Colla-Indep differences toward regions implicated in socioemotional processing. Together, the Quantum Aligned-Misaligned Entanglement Model demonstrates that interbrain connectivity dynamics during memory encoding are context sensitive, dynamically evolving with cooperative engagement, and can be reshaped by empathic interaction in ways that systematically relate to subsequent retrieval performance. These findings suggest that quantum-inspired entanglement can be applied to modeling interbrain neural connectivity, offering a framework for understanding collaborative memory encoding.